2021
DOI: 10.32598/cmja.11.1.995.1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aerobic Exercise and Hydroalcoholic Extract of Tribulus Terrestris on Mitochondrial Oxidative Stress Markers in Heart Tissue of Rats Poisoned With Hydrogen Peroxide

Abstract: Objective: Oxidative stress can cause DNA damage and apoptosis, and leads to cardiovascular disease. This study aims to evaluate the effect of aerobic exercise combined with consumption of hydroalcoholic extract of tribulus terrestris on mitochondrial oxidative stress markers in heart tissue of rats poisoned with hydrogen peroxide. Methods: This is an experimental study conducted on 42 male Wistar rats divided randomly into seven groups of Control (poisoned without supplementation), Aerobic Exercise, Aerobic E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Today, the reduction of oxidative stress and improving the antioxidant system with antioxidant supplements and exercise training are of great interest (12). Antioxidant supplements neutralize ROS by donating an electron or hydrogen atom and regulate SOD, CAT, and GPX enzymes (13,42,43). They also increase the expression of antioxidant enzymes, including those involved in glutathione synthesis, by regulating the NRF2/KEAP1 pathway (14,44).…”
Section: The Effect Of Antioxidant Supplements and Exercise On Muscle...mentioning
confidence: 99%
See 2 more Smart Citations
“…Today, the reduction of oxidative stress and improving the antioxidant system with antioxidant supplements and exercise training are of great interest (12). Antioxidant supplements neutralize ROS by donating an electron or hydrogen atom and regulate SOD, CAT, and GPX enzymes (13,42,43). They also increase the expression of antioxidant enzymes, including those involved in glutathione synthesis, by regulating the NRF2/KEAP1 pathway (14,44).…”
Section: The Effect Of Antioxidant Supplements and Exercise On Muscle...mentioning
confidence: 99%
“…However, physical activity and herbal supplements can have synergistic effects. Delfani et al found in research that aerobic exercise and thistle plant extract can help to improve redox and reduce the oxidative stress of lung tissue (13). However, in a study on old rats, Razavimajd et al concluded that aerobic physical activity and garlic supplementation separately had a protective effect on the heart tissue of rats, but combined interventions did not have a synergistic effect (50).…”
Section: The Effect Of Antioxidant Supplements and Exercise On Muscle...mentioning
confidence: 99%
See 1 more Smart Citation
“…Although ROS production increases during intense physical exercise, the improvement and development of the antioxidant defense system are created parallel to this increase, protecting the tissues against the damage caused by ROS (1,2). However, increased levels of ROS and low activity of antioxidant enzymes, including superoxide dismutase (SOD), glutathione peroxidase (GPX) and catalase (CAT), are considered indicators of oxidative stress (4,5). Studies confirm that oxidative stress plays a role in obesity-related complications (6).…”
Section: Introductionmentioning
confidence: 99%